Economic valuation of area management Latuppa Nature Tourism Palopo City. Issue 1 (November 2021) - Asniana,; Supratman,; Achmad, Amran
Abstract: The Latuppa Nature Tourism Area of Palopo City is an area designated as a tourist destination for the community, both local and from outside the Palopo City area. Various tourist objects are available in this area, both naturally formed such as the Latuppa River flow with several tourist spots, as well as natural panoramas in the form of forests and other landscapes, which are spread in 3 villages, namely Latuppa Village, Murante Village and Kambo Village, Mungkajang District, Kota Palopo. The existence of this area provides added value to the regional income of Palopo City. However, this added value has not been measured quantitatively so that research efforts are needed on the economic assessment of this natural tourist area. The methodology used in this research is quantitative descriptive by observing every tourist spot in the Latuppa natural tourism area, including the Water Boom Hotel Agrowisata, Kambo Highland Inn, Babak Waterfall, and the Natural Baths of the Jodoh River. The factors that influence the number of visits to the Latuppa Nature Tourism location are travel costs, and socio-economic factors of the community. The calculation of the economic value for the natural tourism area uses the Travel Cost Method (TCM), from the analysis results obtained the Economic Value of the Latuppa Nature Tourism Area is Rp. 311, 574, 900. It is hoped that the results of this study can be a reference for the local government of Palopo City in the context of developing and preserving the Latuppa nature tourism area.